Quantification of soil aggregate carbon in tectona grandis (Linn. f) plantation at University of Ibadan, Ibadan, Nigeria (2016)
Forest soils are important reservoir for carbon and contribute to global climate mitigation. Fine clay size aggregate is considered a major determinant of soil carbon distribution. Other aggregate sizes are also important in carbon distribution and estimation. Therefore, soil carbon accumulation of aggregate sizes was quantified at two soil depths in Tectona grandis plantation. Six (30 x 30m') plots were randomly demarcated in the plantation and 360 topsoil and subsoil samples were used for this study. Soil core samples were collected at 4 comers and centre of each plot to depths of0-15,15-30 cm in each plot for period of five months. Soil core samples were oven dried at 105 °C. Soil bulk density and moisture content were estimated from the core samples. Soil sample (100g) from each core sample was sieved into >2,2-1,1-0.5,0.5-0.050 and <0.050 mm aggregate size fractions using dry sieve procedure and proportions estimated. Sub-sample (10g) of each fraction was combusted in Muffle furnace at 500 °C for at least 4 hours and carbon content estimated. Carbon concentration of the bulk soil was also determined. Data were analysed using descriptive statistics and ANOVA at a0 05 Bulk density ranged from 1.08 to 1.33 and 1.39 to 1.54 g/cm3 for subsoil and topsoil, respectively. Soil moisture content ranged from 17.23 to 23.36 and 14.08 to 22.15 cm for topsoil and subsoil, respectively. The 0.5-0.05 mm fraction had the highest values at top and subsoils (39 and 28% of the soil by weight, respectively) followed by 1 -0.5mm size fraction (27% of the soil by weight) at the topsoil and >2mm fraction (27% of the soil by weight) at the subsoil. Topsoil and subsoil had approximately the same proportion of 2-1mm and <50µm fractions. Fine silt (<0.05mm) fraction had the highest soil carbon concentration followed by sand size fraction (>2.0mm) and silt-size fraction (2-lmm) in topsoil and (0.5-0.05mm) in subsoil. The soil carbon associated with <0.05mm was greater than the >2mm fractions. The coefficient of Variation of carbon content were higher among the aggregates of subsoil than topsoil. The mean values of carbon content of bulk soil in topsoil were high than subsoil. Carbon concentration of fine silt size aggregate (0.5-0.05 mm) accurately estimate carbon content of topsoil and subsoil. Moisture content of the bulk soil influence carbon concentration of aggregate size of 1 mm and 0.05.